Path of the prophets : the ethics-driven life - Schwartz, Barry L. (University of Nebraska Press, 2018)
"Devoted to the legacy of the biblical prophets, identifies the prophetic moment in the lives of 18 biblical characters, offers up an intimate view of their inner thoughts, illuminates their ethical legacies, and challenges each of us to walk the path of the prophets today"-- Provided by publisher.
Keywords: Bible. -- Prophets -- Criticism, interpretation, etc.; Bible. -- Prophets -- Criticism, interpretation, etc., Jewish.; Bible. -- Prophets; Prophets -- Biography.; Justice -- Biblical teaching.; Jewish ethics -- Biblical teaching.; PROPHETS.; Prophètes -- Biographies.; Morale juive -- Enseignement biblique.; RELIGION -- Biblical Studies -- Old Testament.; RELIGION -- Judaism -- Sacred Writings.; Justice -- Biblical teaching; Prophets; Biographies; Criticism, interpretation, etc.